1987
DOI: 10.5271/sjweh.2075
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of organic solvent vapors in relation to their toxicity.

Abstract: SATO A, NAKAJIMA T. Pharmacokinetics of organic solvent vapors in relation to their toxicit y. Scand J Work Environ Health 13 (1987) 81-93 . The volatility and Iipophilicity by which organi c solvents are distinct from other chemicals constitut e a characteristic pharmacokinetic feature . They enter a living body by inhalation, preferentially distribute in the adipose tissue, and are eliminated by both expirat ion and metabolic degradation. Th is review article is centered on experiment al studies conducted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…Simultaneous exposure to 1,3-butadiene and styrene resuited in an inhibition of the metabolism of 1,3-butadiene only whereas 1,3-butadiene had no effect on the rate of styrene metabolism (Laib et al 1992). In contrast, pretreatment of rats with phenobarbital (Ohtsuji and Ikeda 1971;Andersen et al 1984;Sato and Nakajima 1987;Elovaara et al 1991) and with acetone, 3-methylcholanthrene or with styrene itself (Elovaara et al 1991) resulted in an enhancement of the styrene biotransformation. These observations were made after administration of very high styrene doses at which according to this pharmacokinetic study the capacity of the enzymes was determining the rate of metabolism (Ohtsuji and Ikeda 1971;Andersen et al 1984;Elovaara et al 1991) or in vitro using liver preparations (Sato and Nakajima 1987;Elovaara et al 1991).…”
Section: Effects On Styrene Metabolizing Enzymesmentioning
confidence: 84%
“…Simultaneous exposure to 1,3-butadiene and styrene resuited in an inhibition of the metabolism of 1,3-butadiene only whereas 1,3-butadiene had no effect on the rate of styrene metabolism (Laib et al 1992). In contrast, pretreatment of rats with phenobarbital (Ohtsuji and Ikeda 1971;Andersen et al 1984;Sato and Nakajima 1987;Elovaara et al 1991) and with acetone, 3-methylcholanthrene or with styrene itself (Elovaara et al 1991) resulted in an enhancement of the styrene biotransformation. These observations were made after administration of very high styrene doses at which according to this pharmacokinetic study the capacity of the enzymes was determining the rate of metabolism (Ohtsuji and Ikeda 1971;Andersen et al 1984;Elovaara et al 1991) or in vitro using liver preparations (Sato and Nakajima 1987;Elovaara et al 1991).…”
Section: Effects On Styrene Metabolizing Enzymesmentioning
confidence: 84%
“…For example, and similar to previous studies, we found that not all exposed gasoline workers developed abnormal menstrual characteristics or deranged reproductive hormone profiles. There are multiple interpretations for this finding, including inter-individual differences due to variations in the pulmonary absorption, distribution, action, metabolism and excretion of inhaled gasoline compounds, which further depend on blood gas values and the fat-blood partition coefficient [30].…”
Section: Discussionmentioning
confidence: 99%
“…The toxic nature of these chemicals are dependent on the type of toxicity as well as its potential, whereas the intensity and duration of toxic responses are dependent on the concentration in the target organ, which is determined by the quantitative description of absorption, distribution, metabolism, and excretion of the chemical 1) . Of these factors determined by pharmacokinetics, the metabolism is garnering more and more attention because i) it is essential as a biomarker for exposure in biological monitoring, ii) it determines the halflife of chemical substances inhaled into the body, and iii) metabolic activation often occurs during the metabolic process.…”
Section: Introductionmentioning
confidence: 99%